2010
DOI: 10.1242/dev.041798
|View full text |Cite
|
Sign up to set email alerts
|

Consistent left-right asymmetry cannot be established by late organizers inXenopusunless the late organizer is a conjoined twin

Abstract: SUMMARYHow embryos consistently orient asymmetries of the left-right (LR) axis is an intriguing question, as no macroscopic environmental cues reliably distinguish left from right. Especially unclear are the events coordinating LR patterning with the establishment of the dorsoventral (DV) axes and midline determination in early embryos. In frog embryos, consistent physiological and molecular asymmetries manifest by the second cell cleavage; however, models based on extracellular fluid flow at the node predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 87 publications
(125 reference statements)
2
44
1
Order By: Relevance
“…We showed previously that the penetrance of LR defects increased from 25% to 40% when Xenopus tadpoles with slight axial defects were included for analysis (Vandenberg and Levin, 2010a) and similar results have been reported by others as well (Danos and Yost, 1996; 1995; Lohr et al, 1997). Here, I found that many LR phenotypes occur concurrently with malformations of midline structures (i.e.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We showed previously that the penetrance of LR defects increased from 25% to 40% when Xenopus tadpoles with slight axial defects were included for analysis (Vandenberg and Levin, 2010a) and similar results have been reported by others as well (Danos and Yost, 1996; 1995; Lohr et al, 1997). Here, I found that many LR phenotypes occur concurrently with malformations of midline structures (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that in Xenopus, developmental defects that affect patterning of the other axes can influence orientation of the LR axis (Lohr et al, 1997; Lohr et al, 1998; Vandenberg and Levin, 2010a). To determine whether this is the case for all treatments, I first determined the frequency of developmental problems in EARLY and CILIA treatments.…”
Section: Resultsmentioning
confidence: 99%
“…PCP is an attractive mechanism for LR asymmetry because it can impose the initial orientation of cells or small groups of blastomeres to entire cell fields (Amonlirdviman et al, 2005), as was originally proposed in the ''LR Coordinator'' model (Hyatt and Yost, 1998). A similar mechanism was recently proposed to explain the instructive influence by means of which primary organizers (existing during the initial cytoskeletal rearrangements) can impose correct asymmetry upon secondary organizers induced later in development (which can otherwise correctly pattern all of their axes except the LR; Vandenberg and Levin, 2010). Consistently, it is known that reversal of the blastocoel roof can randomize asymmetry (Yost, 1992), as predicted by the proposal that the embryonic blastoderm polarizes long before neurulation.…”
Section: Amplification: Bioelectric Redistribution Of Morphogens and mentioning
confidence: 91%
“…G,H: Through an as-yet uncharacterized pathway, the localization of morphogens such as serotonin to the right side of the embryo suppresses downstream expression of genes (i.e., Nodal), which are thus expressed only on the left side (G), which eventually leads to asymmetric organ morphogenesis (H). This model can be readily extended to bodyplans where the midline is defined after the initial cleavages are complete by the spread of LR orientation information from coordinator cell(s) by means of planar cell polarity pathways (Aw and Levin, 2009;Vandenberg and Levin, 2010).…”
Section: Cilia and Nodal Flowmentioning
confidence: 99%
See 1 more Smart Citation